Towards More Agile Management: Literature Review of Information Systems as the Pillar of Management Control - EL KEZAZY, Hamza; HILMI, Yassine (Revue Internationale du Chercheur, 2022)
This article provides an in-depth perspective on the integration of information systems in logistic management control. By evaluating the works of eminent researchers, it underscores the crucial importance of this integration in enhancing the operational and strategic performance of organizations. The careful examination of various technologies, from ERP to Business Intelligence systems, highlights their positive impact on key aspects such as visibility, coordination, responsiveness, and logistic decision-making. The diversity of application contexts, illustrated by various case studies, reinforces the idea that the optimal integration approach depends on the specific needs of each organization.